Detection of enterotoxigenic Escherichia coli colonization factor antigen I in stool specimens by an enzyme-linked immunosorbent assay. - Evans, D G (1980)
An enzyme-linked immunosorbent assay (ELISA) was employed to detect and quantitate the fimbrial colonization factor antigen (CFA/I) of enterotoxigenic Escherichia coli in stool specimens obtained from adult cases of diarrhea in which CFA/I-positive E. coli was the known causative agent. The inhibition method, or blocking technique, was used. In this method, a standardized dilution of human anti-CFA/I serum was preincubated with dilutions of stool extract before transfer to CFA/I-coated microtiter plate wells, and then ELISA was performed with alkaline phosphatase-conjugated anti-human immunoglobulin. CFA/I purified from E. coli strain H-10407 (O78:H11) was used. Acute-phase diarrheal stool specimens were found to contain approximately 3.0 mg of antigen (mean value) per g stool, whereas control (CFA/I-negative) specimens contained insignificant amounts (less than 0.03 mg/g) of antigen. Also, CFA/I was detected in culture fluids of CFA/I positive enterotoxigenic E. coli belonging to a variety of serotypes and was undetectable in similar preparations from P-strains (spontaneous CFA/I-negative derivatives) of the same test cultures. Equivalent results were obtained in ELISA tests by using bacterial cells taken from isolated colonies grown on CFA agar. These results indicate that the ELISA technique will be useful for the diagnosis of diarrhea caused by CFA/I-positive enterotoxigenic E. coli.